Fortification of table olive packing with the potential probiotic bacteria Lactobacillus pentosus TOMC-LAB2 - Rodríguez-Gómez, F.; Romero-Gil, V.; García-García, P.; Garrido-Fernández, A.; Arroyo-López, Francisco N. (Frontiers in Microbiology, 2014)
Dairy products are currently the main carriers of probiotic microorganisms to the human body. However, the development of new matrices for probiotic delivery is convenient for intolerant to milk (or its derivatives) and those requiring low-cholesterol diet consumers. The present work focused on the fortification of previously fermented green Spanish style olives with the autochthonous putative probiotic bacteria Lactobacillus pentosus TOMC-LAB2. The fortification was carried out by inoculating the bacteria into the packing brines using Manzanilla fruits from three different processes: i) spontaneously fermented (F1), ii) fermented using L. pentosus TOMC-LAB2 as starter (F2), and iii) spontaneously fermented and then thermally treated (F3). Data showed that all inoculated treatments had higher population levels (5.49, 4.41 and 6.77 log10 cfu/cm2) than their respective controls (1.66, 4.33 and 0.0 log10 cfu/cm2, for F1, F2 and F3 treatments, respectively). The presence of L. pentosus TOMC-LAB2 on olive surface was confirmed by rep-PCR, with a recovery frequency at the end of the shelf life (200 days) of 52.6, 57.9 and 100.0% for F1, F2 and F3 treatments, respectively. Thus, results obtained in this work show the ability of this microorganism to survive under packing conditions for long period of times as well as to colonize the olive surface which is the food finally ingested by consumers. This opens the possibility for the development of a new and simply probiotic fortified olive product.